The SM expected branching ratio for h → γγ and an excess for h → Zγ - Xiao-Gang He; Zhong-Lv Huang; Ming-Wei Li; Chia-Wei Liu (Journal of High Energy Physics)
Abstract The recent measurements of h → Zγ from ATLAS and CMS show an excess of the signal strength μ Z = σ · B obs / σ · B SM $$ {\left(σ \cdotp \mathcal{B}\right)}_{obs}/{\left(σ \cdotp \mathcal{B}\right)}_{SM} $$ = 2.2 ± 0.7, normalized as 1 in the standard model (SM). If confirmed, it would be a signal of new physics (NP) beyond the SM. We study NP explanation for this excess. In general, for a given model, it also affects the process h → γγ. Since the measured branching ratio for this process agrees well with the SM prediction, the model is severely constrained. We find that a minimally fermion singlets and doublet extended NP model can explain simultaneously the current data for h → Zγ and h → γγ. There are two solutions. Although both solutions enhance the amplitude of h → Zγ to the observed one, in one of the solutions the amplitude of h → γγ flips sign to give the observed branching ratio. This seems to be a contrived solution although cannot be ruled out simply using branching ratio measurements alone. However, we find another solution that naturally enhances h → Zγ to the measured value, but keeps the amplitude of h → γγ close to its SM prediction. We also comment on the phenomenology associated with these new fermions.